"Here's Where I Belong" Still, play adaptation of 'East of Eden.' - Friedman-Abeles Photos:::Creator::::::::::::
Cal Trask (Walter McGinn) and Abra Bacon (Heather MacRae) sitting together. This play is an adaptation of Steinbeck's 'East of Eden.' It ran for twenty previews and one night at the Billy Rose Theatre in New York. RESTRICTED USE Digital copy only. No hard copy.